Rapid ecotoxicity and genotoxicity assessment using Macropodus ocellatus cells - Minseon Kim; Ji Ho Park; Byeonghyeon So; Hojun Lee; Jee Hee Yoon; Yoo Jin Lee; Duyeol Kim; Hyung Wook Kwon; Jihae Park; Taejun Han; Sekyung Oh; Yun Haeng Lee; et al. (Toxicological Research, 2026)

The effect of light, aeration and temperature on the growth and phenolic content of cultivated Ecklonia cava gametophytes (Phaeophyceae) and their antioxidant properties - Ilias Semmouri; Hojun Lee; Samira Alahyaribeik; Juan Miguel Baldominos Botas; Phara Claeys; Taejun Han; Colin R. Janssen; Mahta Mirzaei; Jana Asselman; Jihae Park (Journal of Applied Phycology, 2025)

Integrating bioassay and machine learning data for ecological risk assessments of herbicide use on Ulva australis - Hojun Lee; Duc-Viet Nguyen; Eun-Ji Lee; Taejun Han; Jihae Park (Marine Pollution Bulletin, 2025)

Correction to: Harnessing green tide Ulva biomass for carbon dioxide sequestration - Jihae Park; Hojun Lee; De Saeger; Stephen Depuydt; Jana Asselman; Colin Janssen; Philippe M. Heynderickx; Di Wu; Frederik Ronsse; Filip M. G. Tack; Masanori Hiraoka; Lalit K. Pandey; et al. (Reviews in Environmental Science and Bio/Technology, 2024)

Harnessing green tide Ulva biomass for carbon dioxide sequestration - Jihae Park; Hojun Lee; Jonas De Saeger; Stephen Depuydt; Jana Asselman; Colin Janssen; Philippe M. Heynderickx; Di Wu; Frederik Ronsse; Filip M. G. Tack; Masanori Hiraoka; Lalit K. Pandey; et al. (Reviews in Environmental Science and Bio/Technology, 2024)

Harnessing the power of tidal flat diatoms to combat climate change - Jihae Park; Hojun Lee; Jana Asselman; Colin Janssen; Stephen Depuydt; Jonas De Saeger; Thomas Friedl; Koen Sabbe; Wim Vyverman; Catharina J. M. Philippart; Jaime Pitarch; Philippe M. Heynderickx; et al. (Critical Reviews in Environmental Science and Technology, 2024)

Assessing industrial wastewater effluent toxicity using boosting algorithms in machine learning: A case study on ecotoxicity prediction and control strategy development - Duc-Viet Nguyen; Jihae Park; Hojun Lee; Taejun Han; Di Wu (Environmental Pollution, 2024)

Qualitative and quantitative assessment of diatom deformities and protoplasmic condition under metal and metalloid stress - Sudeeksha Negi; Taejun Han; Jihae Park; Elizabeth A. Bergey; Sangeeta; Jyoti Chaubey; Abhishek Kumar; Divyanshi Gupta; Mahima Gupta; Shivangi Singh; Lalit Kumar Pandey (Protoplasma, 2023)

Evaluating ecotoxicological assays for comprehensive risk assessment of toxic metals present in industrial wastewaters in the Republic of Korea - Jihae Park; Kisik Shin; Hojun Lee; Soyeon Choi; Geonhee Kim; Stephen Depuydt; Jonas De Saeger; Philippe M. Heynderickx; Di Wu; Jana Asselman; Colin Janssen; Taejun Han (Science of The Total Environment, 2023)

Extracts of red seaweed, Pyropia yezoensis, inhibit melanogenesis but stimulate collagen synthesis - Jihae Park; Hojun Lee; Soyeon Choi; Lalit K. Pandey; Stephen Depuydt; Jonas De Saeger; Joon-Tae Park; Taejun Han (Journal of Applied Phycology, 2021)

Effects of stocking density on the productivity and nutrient removal of Agarophyton vermiculophyllum in Paralichthys olivaceus biofloc effluent - Sook Kyung Shin; Su-Kyoung Kim; Jun-Hwan Kim; Taejun Han; Charles Yarish; Jang K. Kim (Journal of Applied Phycology, 2020)

Rapid toxicity assessment of six antifouling booster biocides using a microplate-based chlorophyll fluorescence in Undaria pinnatifida gametophytes - Hojun Lee; Stephen Depuydt; Soyeon Choi; Taejun Han; Jihae Park (Ecotoxicology, 2020)

Toward the molecular understanding of the action mechanism of Ascophyllum nodosum extracts on plants - Jonas De Saeger; Stan Van Praet; Danny Vereecke; Jihae Park; Silke Jacques; Taejun Han; Stephen Depuydt (Journal of Applied Phycology, 2020)
The importance of biostimulants, defined as plant growth-promoting agents that differ notably from fertilizers, is increasing steadily because of their potential contribution to a worldwide strategy for securing food production without burdening the environment. Based on folkloric evidence and ethnographic studies, seaweeds have been useful for diverse human activities through time, including medicine and agriculture. Currently, seaweed extracts, especially those derived from the common brown alga Ascophyllum nodosum , represent an interesting category of biostimulants. Although A. nodosum extracts (abbreviated ANEs) are readily used because of their capacity to improve plant growth and to mitigate abiotic and biotic stresses, fundamental insights into how these positive responses are accomplished are still fragmentary. Generally, the effects of ANEs on plants have been attributed to their hormonal content, their micronutrient value, and/or the presence of alga-specific polysaccharides, betaines, polyamines, and phenolic compounds that would, alone or in concert, bring about the observed phenotypic effects. However, only a few of these hypotheses have been validated at the molecular level. Transcriptomics and metabolomics are now emerging as tools to dissect the action mechanisms exerted by ANEs. Here, we provide an overview of the available in planta molecular data that shed light on the pathways modulated by ANEs that promote plant growth and render plants more resilient to diverse stresses, paving the way toward the elucidation of the modus operandi of these extracts.

Toxicity testing of cosmetic ingredients using gametophyte beads of the brown alga Undaria pinnatifida (Laminariales, Phaeophyta) - Hojun Lee; Juseon Lee; Murray T. Brown; Jihae Park; Christophe Vieira; Taejun Han (Journal of Applied Phycology, 2019)

Towards a multi-bioassay-based index for toxicity assessment of fluvial waters - Lalit K. Pandey; Isabelle Lavoie; Soizic Morin; Stephen Depuydt; Jie Lyu; Hojun Lee; Jinho Jung; Dong-Hyuk Yeom; Taejun Han; Jihae Park (Environmental Monitoring and Assessment, 2019)

Special Issue: Abstracts of the 10th International Conference on Environmental Health Science, 12–13 December 2017, Incheon, Republic of Korea - Taejun Han (Toxicology and Environmental Health Sciences, 2017)

The effects of silver and arsenic on antioxidant system in Lemna paucicostata: Different effects on glutathione system - Yunjung Lee; Hyunhee Kim; Saerong Kim; Areum Park; Youn-Jung Kim; Taejun Han; Eun-Mi Choi (Toxicology and Environmental Health Sciences, 2016)

Differences in the oxidative stress and antioxidant responses of three marine macroalgal species upon UV exposure - Jung-Jin Park; Taejun Han; Eun-Mi Choi (Toxicology and Environmental Health Sciences, 2016)

Toxicity tests using the kelp Undaria pinnatifida for heavy metal risk assessment - Jihae Park; Gyo-Sun Jin; Mi Sook Hwang; Murray T. Brown; Taejun Han (Toxicology and Environmental Health Sciences, 2016)

Potential applications of nuisance microalgae blooms - Jang K. Kim; Sreejith Kottuparambil; Sang Hyun Moh; Taek Kyun Lee; Youn-Jung Kim; Jae-Sung Rhee; Eun-Mi Choi; Byung Hoon Kim; Yong Ju Yu; Charles Yarish; Taejun Han (Journal of Applied Phycology, 2015)

The antioxidant response of Lemna paucicostata upon phenol exposure - Saerong Kim; Hyunhee Kim; Areum Park; Ji-Hye Park; Yunjung Lee; Youn-Jung Kim; Taejun Han; Eun-Mi Choi (Toxicology and Environmental Health Sciences, 2015)

Single and interactive effects of the antifouling booster herbicides diuron and Irgarol 1051 on photosynthesis in the marine cyanobacterium, Arthrospira maxima - Sreejith Kottuparambil; Sulah Lee; Taejun Han (Toxicology and Environmental Health Sciences, 2013)

Erratum to: External K+ Deficiency Inhibits Photosynthetic Activity Through Superoxide Anion Production in Protoplasts Isolated from the Thallus of Ulva pertusa - Chang-Hyo Goh; Soon-Ja Oh; Sung-Soo Jun; Taejun Han (Journal of Plant Biology, 2013)

The role of glutathione in dichloromethane toxicity to Lemna paucicostata - Hyun-Hee Kim; Sae-Rong Kim; Areum Park; Taejun Han; Eun-Mi Choi (Toxicology and Environmental Health Sciences, 2013)

The protective effect of laver extract against the UVA- and UVB-induced damage in HaCaT cells - Sun-Ja Yang; Taejun Han; Eun-Mi Choi (Toxicology and Environmental Health Sciences, 2012)

Inter-population comparisons of copper resistance and accumulation in the red seaweed, Gracilariopsis longissima - Murray T. Brown; James E. Newman; Taejun Han (Ecotoxicology, 2012)

Influence of salinity on metal toxicity to Ulva pertusa - Jeong-ju Oh; Eun-Mi Choi; Young-Seok Han; Jeong-Hyun Yoon; Areum Park; Kyosun Jin; Ju-Wook Lee; Hoon Choi; Sunjin Kim; Murray T. Brown; Taejun Han (Toxicology and Environmental Health Sciences, 2012)

Sensitivity of spore germination and germ tube elongation of Saccharina japonica to metal exposure - Taejun Han; Jeong-Ae Kong; Hee-Gyu Kang; Seon-Jin Kim; Gyo-Sun Jin; Hoon Choi; Murray T. Brown (Ecotoxicology, 2011)

A Comparative Study on Toxicity Identification of Industrial Effluents Using Daphnia magna - Xianliang Yi; Eunhee Kim; Hun-Je Jo; Taejun Han; Jinho Jung (Bulletin of Environmental Contamination and Toxicology, 2011)

External K+ Deficiency Inhibits Photosynthetic Activity Through Superoxide Anion Production in Protoplasts Isolated from the Thallus of Ulva pertusa - Chang-Hyo Goh; Soon-Ja Oh; Sung-Soo Jun; Taejun Han (Journal of Plant Biology, 2010)

Photosynthesis and photoinhibition of two green macroalgae with contrasting habitats - Young-Seok Han; Sung Ho Kang; Taejun Han (Journal of Plant Biology, 2007)